Glutamatergic Neurotransmission Controls the Functional Lateralization of the mPFC in the Modulation of Anxiety Induced by Social Defeat Stress in Male Mice - Santos-Costa, Nathália; Baptista-de-Souza, Daniela; Canto-de-Souza, Lucas; Fresca da Costa, Vinícius; Nunes-de-Souza, Ricardo Luiz (Frontiers in Behavioral Neuroscience, 2021)
The left and right medial prefrontal cortex (L & RmPFC) process emotional responses induced by stress-related stimuli, and LmPFC and RmPFC inhibition elicit anxiogenesis and anxiolysis, respectively. Here we sought to investigate (i) the mPFC functional laterality on defensive/anxiogenic-like behaviors in mice subjected to chronic social defeat stress (SDS); (ii) the effects of LmPFC inhibition (with local injection CoCl2) on the RmPFC glutamatergic neuronal activation pattern; and (iii) the effects of the RmPFC NMDA receptor blockade on the anxiety induced by LmPFC inhibition in mice exposed to the elevated plus-maze (EPM). Results showed that chronic SDS induced defensive-like behaviors followed by the rise of ΔFosB labeling and by ΔFosB + CaMKII double-labeling bilaterally in the cingulate (Cg1) and infralimbic (IL) subareas of the mPFC. Chronic SDS also increased ΔFosB and by ΔFosB + CaMKII labeling only on the right prelimbic (PrL). Also, left PrL inhibition increased cFos + CaMKII labeling in the contralateral PrL and IL. Moreover, anxiogenesis induced by the left PrL inhibition was blocked by NMDA receptor antagonist AP7 injected into the right PrL. These findings suggest the lateralized control of the glutamatergic neurotransmission in the modulation of emotional-like responses in mice subjected to chronic SDS.